8th International Conference on compressors and their Systems 2013 (Woodhead Publishing Ltd., 2013)
This book contains the papers from the 2013 International Conference on Compressors and Their Systems, held from 9-10 September at City University London. The long-running conference series is the ultimate global forum for reviewing the latest developments and novel approaches in compressor research. High-quality technical papers are sourced from around the globe, covering technology development, operation, maintenance and reliability, safety and environmental impact, energy efficiency and carbon footprint, system integration and behaviour, upgrades and refurbishment, design and manufacture, education and professional development. All the papers are previously unpublished and constitute leading edge research. Presents leading edge developments in compressor technologyGives the latest prediction and modelling techniquesDetails the new technology and machinery.